Comparison of mean Postoperative Inguinodynia in patients undergoing open Inguinal Hernia Surgery with use of standard Polypropylene Heavy Weight Mesh v/s Ultra Pro light Weight Mesh - Muhammad Awais, Osama Rafi, Saulat Naeem, Ayesha Waheed, Rizwan Khan, Rooh-Ul-Ain, Itrat Hussain Kazmi, Sundas Javeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Various types of meshes for inguinal hernias have been discovered to combat with chronic groin pain related problems. The data regarding these findings was variable due to difference in the cut off values used in the past in different studies to label inguinodynia and local data was scarce where HWM is still highly practiced. Aim: To compare the mean postoperative inguinodynia in patients undergoing open inguinal hernia surgery with use of standard polypropylene heavy weight mesh (HWM) v/s Ultra Pro lightweight mesh (LWM). Methodology: This is a prospective randomized controlled trail conducted at department of surgery, Services Institute of Medical Sciences, from July 2019 to June 2020. Cases were divided in two groups by using radio opaque sealed envelopes labeled as A and B. Group-A underwent Lichtenstein mesh repair by Ultra Pro LWM and group B had polypropylene heavy weight mesh (HWM). Lichtenstein mesh repair was done under spinal or general anesthesia by the experienced surgeon. Duration of surgery was also calculated (from incision to closure). Patient was followed in outpatient department at 3 months where the outcome was seen and inguinodynia was assessed. Results: The mean age was in group A was 40.66±10.52 years and 40.53 ±12.56 years in group B. The mean pain Score in group A was 2.024±0.88 and in Group-B it was 2.97 ±0.85. Conclusion: Ultra Pro LWM is more effective in terms of less postoperative pain as compared to standard polypropylene heavy weight mesh in patients undergoing open inguinal hernia surgery